This I Believe - Ziebarth, E. W. (Tufts Archival Research Center, 2006)
E.W. Ziebarth describes being challenged in high school to write out his beliefs and finds that, years later, his beliefs are just as difficult to pin down; nevertheless, he firmly believes in freedom, the worth and dignity of the individual, and the need to receive generalizations and proproganda with a healthy dose of skepticism.